A NOVEL NON-TOXIC XYLENE SUBSTITUTE (SBO) FOR HISTOLOGY - Kunhua, Wang; Chuming, Fan; Tao, Lao; Yanmei, Yang; Xin, Yang; Xiaoming, Zhang; Xuezhong, Guo; Xun, Lai (African Journal of Traditional, Complementary and Alternative Medicines, 2011)
Xylene has been generally used as a clearing and deparaffinizing agent in histology. Because of the potential toxic and flammable nature of xylene, its substitutes have been introduced into some laboratories. In this study, we introduced a novel, non-toxic xylene substitute (SBO), which was generated through a mixture of 86% of white oil No.2 and 14% of N-heptane. SBO had a high boiling point (188Â°C) and flash point (144Â°C) coupled with a scentless and decreased volatility. To compare the effectiveness of SBO and xylene in histology, a wide range of tissue samples from rats and human beings were processed in parallel in SBO and xylene, subjected to various staining procedures. Similar to the xylene-processed paraffin blocks, the SBO-processed counterparts were easy to section without any evidence of cell shrinkage. Assessment of the SBO-treated sections stained with hematoxylin-eosin revealed a good maintenance of cell morphology and structure, and a clear definition of the cytoplasm and the nucleus. Moreover, comparable good results were achieved between the SBO- and xylene-processed tissues in other histochemical and immunohistochemical stainings. Six-month clinical applications at one department of pathology supported the potentials of SBO as a xylene substitute. In conclusion, we suggest that SBO is a safe and efficient substitute of xylene and may probably replace xylene without losing valuable diagnostic information.